Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Systematic biotic responses to palaeoenvironmental change in the Late Pleistocene southern South China Sea: a preliminary study - Muhong Chen; Qianyu Li; Lanlan Zhang; Fan Zheng; Jun Lu; Rong Xiang; Lili Zhang; Wen Yan; Zhong Chen; Shangbin Xiao (Journal of Quaternary Science, 2008)
Oxygen and carbon isotopes from the planktonic foraminifer Globigerinoides sacculifer , trace element contents, calcium carbonate, biogenic silica, grain size, and abundances of diatoms, radiolarians and foraminifera in a deep‐sea core from the southwestern South China Sea were analysed to investigate the response of various marine ecological communities to environmental changes over the last 200 ka. The synthesised results show that the quality of the palaeoecological environment for biological growth is primarily affected by nutrient supply and terrigenous disturbance. Ba and P are important nutrient elements for the growth of diatoms, radiolarians and planktonic foraminifera. Together with dissolved silica and calcium carbonate in sea water, these elements may control microbiotic development. However, variations in Fe content appear to affect diatom and radiolarian abundance. Optimal biotic growth occurs when nutrients are abundant and when there is minimal terrigenous disturbance. Biotic growth decreases when sea water is highly oligotrophic and terrigenous input is high. Maximum biological growth occurred in the mid Holocene, but deteriorated soon afterwards owing to increased terrigenous input, causing a decrease of biological abundance and productivity in the late Holocene. The results also indicate how the Toba volcanic eruption ca. 74 ka ago contributed to changing the ecological environment in the southern South China Sea. Copyright © 2008 John Wiley & Sons, Ltd.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Microbial composition and diversity of an upland red soil under long-term fertilization treatments as revealed by culture-dependent and culture-independent approaches - Ji-Zheng He; Yong Zheng; Cheng-Rong Chen; Yuan-Qiu He; Li-Mei Zhang (Journal of Soils and Sediments, 2008)

A novel cytotoxic monoterpenoid from the leaves of Cinnamomum subavenium - Rong-Jyh Lin; Wen-Li Lo; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Cytotoxic activity of Ipomoea cairica - Rong-Jyh Lin; Chung-Yi Chen; Wen-Li Lo (Natural Product Research, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Thrombin-induced microglial activation contributes to the degeneration of nigral dopaminergic neurons in vivo - Cheng-Fang Huang; Gang Li; Rong Ma; Sheng-Gang Sun; Jian-Guo Chen (Neuroscience Bulletin, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Persistence and dissipation of synthetic pyrethroid pesticides in red soils from the Yangtze River Delta area - Xiao-zhi Gu; Gang-ya Zhang; Li Chen; Rong-ling Dai; Yuan-chun Yu (Environmental Geochemistry and Health, 2008)